The association between treated psychiatric and neurodevelopmental disorders and out-of-home care among Finnish children born in 1997. - Kääriälä, Antti; Gyllenberg, David; Sund, Reijo; Pekkarinen, Elina; Keski-Säntti, Markus; Ristikari, Tiina; Heino, Tarja; Sourander, Andre (European Child & Adolescent Psychiatry, 2022)
Comprehensive overviews of the use of psychiatric services among children and adolescents placed in out-of-home care (OHC) by child welfare authorities are scarce. We examine specialized service use for psychiatric and neurodevelopmental disorders among children and adolescents in a total population involving children in OHC. We used the longitudinal administrative data of a complete Finnish birth cohort 1997 (N = 57,174). We estimated risk ratios (RRs) for a range of diagnosed psychiatric and neurodevelopmental disorders among children in OHC. We also estimated RRs for OHC among those with diagnosed disorders. We used descriptive methods to explore the timing of first entry into OHC relative to the first diagnosis. Among children in OHC, 61.9% were diagnosed with any psychiatric or neurodevelopmental disorder, compared with 18.0% among those never in OHC (RR: 3.7; 95% CI 3.6–3.8). The most common diagnosed disorders among children in OHC were depression and anxiety disorders, neurodevelopmental disorders, and oppositional defiant disorder/conduct disorder (ODD/CD). Among all children with any diagnosis, 18.1% experienced OHC, compared with 2.5% among those without a diagnosis (RR: 7.4; 95% CI 6.9–7.9). Of those diagnosed with self-harm and suicidality, ODD/CD, substance-related disorders, and psychotic and bipolar disorders, 43.5–61.2% experienced OHC. Of the children in OHC receiving psychiatric services, half were diagnosed before first placement in OHC. The majority of children with experience in OHC were diagnosed with psychiatric or neurodevelopmental disorders. They comprised a significant proportion of individuals treated for severe and complex psychiatric disorders and self-harm.